Improving Understanding of Islamic Cultural History Subjects Through Discussion Methods - Sodikin, Sodikin (Research Journal on Teacher Professional Development, 2024)
ABSTRACT Based on the results of observations and interviews with students and teachers of the Islamic Cultural History subject that had been conducted at MTs Assa'adah Gunung Sugih, Central Lampung, it turned out that the problems encountered in schools were a lack of focus in learning. Given these problems, the researcher wants to take an approach by applying the discussion method. This research uses classroom action research, the learning outcomes are in the form of values. The research was conducted in 3 cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. Each cycle is carried out 1 meeting. In cycle I of the 36 students who took the test there were 10 students who did not complete. Because there were still some students who had not finished, the researcher continued to cycle II. And if it has not been completed, then it will be continued in cycle III.